2021
DOI: 10.37506/ijfmt.v15i4.16756
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection between Entamoeba histolytica and Helicobacter Pylori in Patients at Wasit Province

Abstract: The current study was conducted at Wasit province, Iraq during the period from 28 October 2020 to 28 December 2020. The study included one hundred stool samples taken from questionable patients of Entamoeba histolytica and Helicobacter pylori. Samples were collected from patient attended to General Hospital of Martyr Fairuz at Hay district , Saeed Health center and Hospital of Al-Kut. All samples have been checked using direct smear lugol's iodine stain for Entamoeba histolytica and dipstick for Helicobacter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The reason for the difference may be attributed to many reasons, the most important of which are the service and environmental situation, as well as public hygiene, attention to personal culture, and the difference in the standard of living and social. The highest prevalence of E.histolytica infection (46 %) was among the age group (<50) years old followed by (41-50) years (27%), then (31-40)years (20%) and finally (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years old (7%).Our information was incompatible to (22,23).…”
Section: -Results and Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The reason for the difference may be attributed to many reasons, the most important of which are the service and environmental situation, as well as public hygiene, attention to personal culture, and the difference in the standard of living and social. The highest prevalence of E.histolytica infection (46 %) was among the age group (<50) years old followed by (41-50) years (27%), then (31-40)years (20%) and finally (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years old (7%).Our information was incompatible to (22,23).…”
Section: -Results and Discussioncontrasting
confidence: 54%
“…The total infection rate with E.histolytica was 30%. It was found that the highest rate of infection with E.histolytica was within the age group (<50) years, it reach 14%, and the lowest infection rate was within the age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years with a rate of 2 %, the study agreed with (20) who showed a difference in the infection rate, as the percentage of tissue type amoeba infection was recorded at 24.85% in the city of Kirkuk, but it disagreed with ( 21) who showed that the total infection rate with intestinal parasites was 13.64%. The incidence of infection in the current study is high compared to results of previous studies.…”
Section: -Results and Discussionmentioning
confidence: 99%